lncRNA-SNHG14 Plays a Role in Acute Lung Injury Induced by Lipopolysaccharide through Regulating Autophagy via miR-223-3p/Foxo3a - Jun Hong; Shijing Mo; Fangxiao Gong; Zongbin Lin; Hanhui Cai; Ziqiang Shao; Xianghong Yang; Renhua Sun; Qiangnu Zhang; Jingquan Liu (Mediators of Inflammation)
lncRNAs play important roles in lipopolysaccharide- (LPS-) induced acute lung injury. But the mechanism still needs further research. In the present study, we investigate the functional role of the lncRNA-SNHG14/miR-223-3p/Foxo3a pathway in LPS-induced ALI and tried to confirm its regulatory effect on autophagy. Transcriptomic profile changes were identified by RNA-seq in LPS-treated alveolar type II epithelial cells. The expression changes of lncRNA-SNHG14/miR-223-3p/Foxo3a were confirmed using qRT-PCR and west blot. The binding relationship of lncRNA-SNHG14/miR-223-3p/and miR-223-3p/Foxo3a was verified using dual-luciferase reporter, RNA immunoprecipitation, and RNA pull-down assays. Using gain-of-function or loss-of-function approaches, the effect of lncRNA-SNHG14/miR-223-3p/Foxo3a was investigated in LPS-induced acute lung injury mice model and in vitro. Increasing of lncRNA-SNHG14 and Foxo3a with reducing miR-223-3p was found in LPS-treated A549 cells and lung tissue collected from the LPS-induced ALI model. lncRNA-SNHG14 inhibited miR-223-3p but promoted Foxo3a expression as a ceRNA. Artificially changes of lncRNA-SNHG14/miR-223-3p/Foxo3a pathway promoted or protected cell injury from LPS in vivo and in vitro. Autophagy activity could be influenced by lncRNA-SNHG14/miR-223-3p/Foxo3a pathway in cells with or without LPS treatment. In conclusion, aberrant expression changes of lncRNA-SNHG14 participated alveolar type II epithelial cell injury and acute lung injury induced by LPS through regulating autophagy. One underlying mechanism is that lncRNA-SNHG14 regulated autophagy by controlling miR-223-3p/Foxo3a as a ceRNA. It suggested that lncRNA-SNHG14 may serve as a potential therapeutic target for patients with sepsis-induced ALI.